Evidence for at least two dominant neutralization antigens on human rhinovirus 14. - Sherry, B (1985)
A collection of 28 mutants of human rhinovirus 14, selected for resistance to 10 individual neutralizing monoclonal antibodies, was used to identify two major neutralization antigens, N-Ag I and N-Ag II. Isoelectric analysis showed that all 16 of the N-Ag I mutants analyzed were charge altered in VP1;8 of 12 N-Ag II mutants were altered in VP3. These results suggest that N-Ag I resides on VP1, whereas N-Ag II lies on VP3. The frequency of charge alterations was much higher than predicted by the genetic code, suggesting that charged amino acids on the antigenic sites play an important role in interaction with neutralizing antibody. Antibodies against N-Ag I and N-Ag II neutralize with widely different efficiencies.